Opportunity and Challenges of Pasupatinath's Pilgrimage Tourism (Interdisciplinary Research in Education, 2021)
Pilgrimage in Hindu tradition is called tirthayatra. Tirhayatra is awarded different meanings depending on the sect, region and tradition. Scholars have described various typological schemes for tirthayatra that derive from Sanskrit texts such as SkandaPurana. Pilgrimage could be defined as ‘A journey resulting from religious causes, externally to a holy site, and internally for spiritual purposes and internal understanding’.  To the Hindu it is the holy land of the PashupatiNath. Many Grant philosophers-saints like Vayas, Valmiki, Viswamitra, Pulah, Pulasta ,Koushik, Kapil, Yajnavalka, Suka, Sanakadi and Raja Janak found endless spiritual inspiration while penancing by the sacred bank of Koshi, Krishna Gandaki, Bagmati and Sarada rivers or in the pristine Himalaya mountain. All these great thinkers attained perfection in their spirituality here. PashupatiNath is the holiest of all the shrines devoted to lord Shiva, the guardian deity of Nepal. This study was based on field survey and secondary sources of information. The study based on both descriptive and analytical as well both qualitative and quantitative information was used. Questionnaire, in-depth interview and FGD applied with PashupatikshetrabikasKosha, MoolBhatta of Pashupatinath, export of pilgrimage tourism sectors and related persons were also conducted in the field visiting site.100 Respondents were randomly selected from pashupatinath.  Sources of income, source of employee, destination after Char Dham, center for pilgrimage and hotpot destination of Hinduismare the major opportunities of pilgrimage tourism of Pashupatinath as well as Mela management, pollution, waste management,beggar’s management, drinking water and toilet use are the major challenge of pashupatinath.